The Effect of E-Perceived Price, E-Perceived Quality and E-Perceived Value on Repurchase Intention of Spotify Premium Users in The Greater Bandung Area - Valens Zhen Fabian; Leni Evangalista Marliani (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This research explores the elements affecting the repurchase intention of Spotify Premium users in the Greater Bandung region. As digital music streaming platforms expand quickly, it has become more crucial for scholars and professionals to comprehend the elements that motivate users to keep their subscriptions. This study examines how e-perceived price, e-perceived quality, and e-perceived value influence the intention to repurchase among Spotify Premium subscribers. A quantitative method was used by handing out structured questionnaires to 147 Spotify Premium users in Greater Bandung. The gathered data underwent analysis through Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings show that e-perceived price (β = 0.215, p = 0.002), e-perceived quality (β = 0.341, p < 0.001), and e-perceived value (β = 0.387, p < 0.001) exhibit positive and significant impacts on repurchase intention. Among these factors, e-perceived value appeared as the most significant predictor of repurchase intention, succeeded by e-perceived quality and e-perceived price. Additionally, the model shows significant explanatory capability, boasting an R² value of 0.842, which signifies that 84.2% of the variation in repurchase intention is accounted for by the three predictor variables. These results indicate that users are inclined to renew their Spotify Premium subscriptions when they recognize significant value, excellent service quality, and fair pricing. Thus, Spotify must concentrate on increasing customer value by offering personalized features, ongoing service enhancements, and pricing strategies that meet users’ expectations to bolster customer retention and promote subscription renewals. Keywords: Online perceived price; Online perceived quality; Online perceived value; Intent to repurchase; Spotify Premium.